A simple and practical method to determine peroxide values in edible oils via infrared quartz cuvette-based Fourier transform infrared spectroscopy. Issue 29 (13th July 2018) - Shang, Jing; Wu, Xinran; Hu, Keqing; Huyan, Zongyao; Li, Qi; Yu, Xiuzhu
Abstract : A rapid and simple method was developed to determine the peroxide values (PVs) of edible oils by Fourier transform infrared spectroscopy. The spectra of edible oils were obtained using an infrared quartz cuvette (IQC) as a spectral accessory. The IQC-based FTIR method is more feasible and accurate than the traditional method. Abstract : A rapid and simple method was developed to determine the peroxide values (PVs) of edible oils by Fourier transform infrared (FTIR) spectroscopy. The spectra of edible oils were obtained using an infrared quartz cuvette (IQC) with a thickness of 10 mm as a spectral accessory. PV calibration was developed using partial least squares (PLS) and validated using the standard method of American oil chemists' society. The results showed that the spectral range of O–H from 3763 cm −1 to 3260 cm −1 was optimal for PLS PV calibration. The correlation coefficients of the blind samples and determined stability were close to 1, and the root mean square error of calibration and validation was low. These findings indicate that the IQC-based FTIR method is more feasible and accurate than the traditional method.